Alcohol withdrawal and brain stroke risk: A comparative study of sociodemographic and clinical profiles in a tertiary care setting - Pancheti Narayana; Ravikanth Pula; Rakesh Kathgave (Telangana Journal of Psychiatry, 2026)
ABSTRACT Background: Alcohol dependence with withdrawal state is associated with more hemorrhagic strokes and right-sided strokes. Alcohol withdrawal-related cerebrovascular accident (CVA) is 2–3 times more common in young males and urban areas. Methodology: This cross-sectional study was conducted in the neurology and psychiatry departments of a tertiary care hospital in South India after obtaining ethical approval and written informed consent. Participants were recruited through random sampling, with 75 cerebral vascular accident (CVA) patients with alcohol dependence with withdrawal (CWW) and 75 CVA patients without alcohol dependence with withdrawal (CAS) as controls. Results: The CWW group was significantly younger (mean age 49.48 ± 7.41 vs. 52.93 ± 9.35; P = 0.01) and predominantly male (93.33% vs. 64% females in CAS; P = 0.0001). Hemorrhagic CVA was more prevalent in CWW (62.66% vs. 5.33% in CAS; P = 0.0001), while ischemic CVA dominated the CAS group (94.66% vs. 37.33% in CWW; P = 0.0001). Recurrent CVA was higher in CWW (20% vs. 6.66%; P = 0.029). Comorbidities such as diabetes (24% vs. 50.7%; P = 0.01) and hypertension (57.3% vs. 69.3%; P = 0.17) were less frequent in CWW. Conclusion: As hypothesized, CVA with alcohol dependence withdrawal predominantly affects young males, with hemorrhagic strokes being more common in this group compared to controls. These subjects also showed fewer medical comorbidities like hypertension. Significant differences between groups included higher rates of hemorrhagic CVA and cerebellar CVA in CWW subjects, while hypertension was more common in CAS.